2023
DOI: 10.1002/cbdv.202300264
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Activity and Mechanism of Action of Sargassum fusiforme Polysaccharides

Abstract: Sargassum fusiforme polysaccharide (SFP) is a kind of biologically active macromolecule with biological functions. In this study, oxidative stress and high‐fat HepG2 cell models were established to investigate its lipid‐lowering activity and mechanism of action. It was found that SFP and its two isolated fractions had antioxidant effects on the cells. It was also found the polysaccharides decreased the content of total cholesterol and total triglyceride in the high‐fat cells. RT‐qPCR assays revealed that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Hyperlipidaemia can induce the occurrence of atherosclerosis, which causes cardiovascular and cerebrovascular disorders (Tang, Jiang et al, 2023), thus becoming a major public health concern. Earlier studies revealed that many sulfate rich seaweed polysaccharides showed potent hypolipidemic effects with different action mechanisms.…”
Section: Hypolipidemic Activitymentioning
confidence: 99%
“…Hyperlipidaemia can induce the occurrence of atherosclerosis, which causes cardiovascular and cerebrovascular disorders (Tang, Jiang et al, 2023), thus becoming a major public health concern. Earlier studies revealed that many sulfate rich seaweed polysaccharides showed potent hypolipidemic effects with different action mechanisms.…”
Section: Hypolipidemic Activitymentioning
confidence: 99%